Experimental investigation of aerodynamics behavior of a new generic of unmanned air vehicle (heliplane) - Djamel Kaddouri; Benlefki Abdelkrim; Adjlout Lahouari; Mokhtari Abdellah (Journal of Mechanical Engineering and Sciences, 2022)
The aeronautics studies and particularly the development of drones represent an important field, in which there is a very large number of research and studies.This article aims to present an experimental aerodynamic study of an autonomous surveillance unmanned aerial vehicle (UAV) that is capable of combining the advantages of both categories, namely the fixed-wing drones and the rotary-wing drones. To achieve this objective, a wind tunnel was used to study the flow around this drone in order to better understand the aerodynamic phenomena and to obtain some initial estimates of the lift, drag and moment coefficients, at three different Reynolds numbers of 4.02×104, 6.03×104 and 8.04×104, and for different angles of attack, from [−45°, +45°] with step of 1°.The experimental results obtained in this work show an casi-symetrical variation bertwen the negatif and positif incidence angles of the lift coeffecient, wiche indicate that the heliplane can fly in an inverted position, whatever the angle of incidence. Moreover, the minimum mean value of drag coeffecient according 1° incidence angle is 0.0478 then the drag due to geometry and pitching moment can never be canceled.